Navigating The Complexities of Mut’ah Marriages: The Role of West Java’s Local Government in Protecting Communities - Dadang Syaripudin; Encang Saefudin (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2023)
Adultery is one of the reasons Islam pays excellent attention to marriage. The danger due to adultery is very great, as well as being categorised as a major sin that Allah SWT hates. Islam really expects all forms of adultery, let alone an act of adultery that is defended and justified and packed with values ​​that seem to be true. Mut'ah marriage, which often occurs in the peak tourist area, which is known as the